Intersections between Ubuntu and Social Work in Humanitarian Settings in Uganda: A Decoloniality Perspective (Journal of Comparative Social Work, 2025)
Understanding the context and complexities of humanitarian settings and the intersections between Ubuntu and social work is crucial, yet it has not received considerable attention in Africa. With the increasing number of refugees in African countries such as Uganda, it is imperative to examine how Ubuntu manifests itself in humanitarian responses, and how it shapes social work interventions in these contexts. This paper investigates the interface between Ubuntu and social work values, focusing on how this influences the reception of refugees and their interactions with authorities, service providers and host communities. It further explores how Ubuntu and social work intersect to help facilitate the social integration of refugees into host communities, particularly in protracted refugee situations. The study employs a qualitative approach, integrating a desk review of 60 scholarly publications and primary data from semi-structured interviews with refugees and key informants. Using an intersectional lens, we analyse how Ubuntu is understood and practiced, and how it mutually influences social work values in humanitarian settings. Findings reveal that Ubuntu fosters collective responsibility, shared humanity and solidarity, which aligns with social work values of empathy and mutual respect, facilitating the integration of refugees into host communities. However, certain aspects of Ubuntu, such as communal decision-making, may conflict with social work’s emphasis on individual agency and self-determination. By situating the discussion within the framework of decoloniality, the study highlights how the cultural resources embedded in Ubuntu can contribute to the indigenization and decolonization of social work practices, while critically examining aspects of Ubuntu that may conflict with social work values, such as self-determination and individual agency, emphasizing the need for cautious engagement with these tensions.